Differences in Clinical Presentation among Persons with Pulmonary Tuberculosis: A Comparison of Documented and Undocumented Foreign-born to US-born Persons - Achkar, Jacqueline M (2008)
BACKGROUND: Most tuberculosis (TB) cases in the US are diagnosed in foreign-born persons, and undocumented foreign-born may face particular barriers to timely access to health services. This study investigates whether differences in clinical presentations among persons with pulmonary TB (PTB) are associated with foreign-birth or documentation status. METHODS: In this cross-sectional study, we reviewed the medical records of patients diagnosed with microbiologically proven PTB at a New York City public hospital between April 1999 and March 2005. Three groups with PTB: US-born, foreign-born with documents, and undocumented, were defined at presentation and compared. Odds ratios (ORs) for the presence of symptom duration ≥8 weeks prior to hospital admission for each group were estimated using logistic regression. RESULTS: Among 194 subjects with newly diagnosed PTB, 61 (31%) were US-born, 62 (32%) were documented, and 71 (37%) were undocumented foreign-born. Undocumented persons presented with significantly higher frequencies of cough (p=0.020) and hemoptysis (p=0.012), and had a significantly longer median duration of symptoms compared to US-born (8 versus 4 weeks; p=0.023). No significant differences between documented foreign-born and US-born were observed. In multivariate analysis, being undocumented relative to US-born (OR(adj) 4.1, 95% CI 1.7–10.2; p=0.002) and being unemployed (OR(adj) 2.2, 95% CI 1.1–4.5; p=0.023) were independently associated with prolonged symptom duration ≥8 weeks. CONCLUSION: An undocumented status is associated with increased frequency of cough and hemoptysis, and longer symptom duration prior to hospital evaluation for PTB. Whether reducing barriers to health services for undocumented persons could enhance TB control deserves further study.